The ‘C’ Word Understanding the Context of Mental Distress (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
Why is context important? Because, without it, we fill in the blanks and arrive at erroneous conclusions. That is precisely what psychiatry has done with our distress. By second-guessing ‘scientific evidence’ that has so far proved elusive, they have sent us on a wild goose chase, diverting everyone’s attention from the causal factors that are right before our eyes. Instinctively we know this but it has suited us, as a society and as individuals, to ignore it and bow instead to the ‘expertise’ of those whose professional, financial and political motives we neglect to examine. This article attempts to redress the balance by speaking frankly from my experience of coming through the psychiatric system to emerge with a clearer understanding of the damage that is done by medicalising our distress.